(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The Naqshbandiyya is one of the most influential Sunni Sufi orders in Islamic history. Originating in Bukhara, it emphasizes silent dhikr (remembrance of God), moral discipline, and strict adherence to Sharia. This paper explores the historical emergence of the order, its unique spiritual methodology, and its broad influence across Muslim societies. Special attention is given to its evolution through branches like Khalidi and Haqqani, and its adaptability to modern contexts. The study highlights how the Naqshbandi order successfully combined inner spiritual reform with public activism, shaping both individual lives and broader societal developments.